Studies of mass transfer coefficients in denitrifying biofilms - García López, L. A. (2000)
Mass transfer coefficients within denitrifying biofilms were determined with an inert compound (LiCl) using two different flow conditions in a membrane flow cell and feeding an easily degradable substrate. The experiments were made until the biofilm reached steady state. The results obtained from the biofilm mass transfer experiments show that the biofilms grown under these two different conditions reach similar values in the steady state. However, the mass transport was higher during biofilm formation, for the biofilm developed under higher upflow velocity.